Pendampingan Pola Asuh Orang Tua pada Ibu-Ibu di Kelurahan Serengan Surakarta - Siti Rokhimah (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2022)
Parenting is one of the spearheads of parents efforts in educating children. Children who are educated with the right parenting style will become good children. Otherwise, children who are educated with bad parenting will make children who are not good. This parenting style assistance is carried out using counseling methods and approaches through several stages, including, 1) planning activity programs; 2) implementation of the activity plan; 3) implementation of evaluation and reporting of activities. This assistance is an effort to increase the insight of parents, especially mothers about parenting, and increase the ability of parents to make decisions in implementing the type of parenting that will be applied to their children.